Dinamika Governance Rantai Nilai dalam Upaya Peningkatan Daya Saing Global Industri Minyak Nilam Provinsi Aceh - , Heriani; , Dr. Nanang Pamuji M. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Indonesia is the world's major supplier of patchouli oil, because nearly 90% of the world Patchouli are produced by Indonesia, the primary demand for oil is Acehâs patchouli (Nilam Aceh ), which has the quality and flavor that is unmatched by any other patchouli oil in the world. Because it is a single producer, Indonesia should have the power to determine the price of patchouli oil, good prices in global markets, local farmers until the price level. But the reality of what happened, patchouli prices continue fluctuated, although high in the international market, the prices obtained by farmers who did not experience significan.it increase due to the value chain controlled by the party who just wants his own advantage. By using qualitative research methods, this study seeks to explain about the dynamics governance of Aceh Patchouli industry of value chain in an effort to increase global competitiveness. What I want to be known by this study is the governance actor of Aceh Patchouli industry value chain which has a major role in upgrading. Allegedly, the central government and local governments in Aceh Province as the main pillars of governance which has the ultimate authority does not take a leading role to intervene in the value chain in an effort to increase global competitiveness of Aceh Patchouli oil industry. The conclusion this research is the minimal role of government, both central and local governance in Aceh Province in the value chain, it is caused by three things, first the lack of specific policies regarding industry patchouli oil, patchouli oil is a commodity when the potential for the country. Second, Aceh's provincial government took no action to export the commodity nilamnya itself, proved to Medan was still master of patchouli oil trade system in Aceh. And lastly, a more dominating role of the NGO interventions in Aceh patchouli oil industry of value chain.